2012
DOI: 10.1111/jfpp.12006
|View full text |Cite
|
Sign up to set email alerts
|

Betalain Content and Antioxidant Activity of Beta vulgaris : Effect of Hot Air Convective Drying and Storage

Abstract: Beet root (Beta vulgaris) powder is a good natural food colorant because it contains significant amounts of red‐colored betalain pigments. There is increasing interest in the use of natural food colors, which provide health benefits like antioxidant activity. This article reports a study of the effects of convective hot air drying on retention of betalain pigments and antioxidant activity. A wide range of drying temperatures (50–120C) was used for the study. Drying at 50–65C gave best pigment retention (betacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 11 publications
7
44
1
Order By: Relevance
“…Ghokale & Lele (2014) studied the effect of drying at temperatures from 50 to 120 °C on betalain retention and found that, at lower temperatures, there was lower degradation of these constituents, corroborating the results of the present study.…”
Section: Resultssupporting
confidence: 78%
“…Ghokale & Lele (2014) studied the effect of drying at temperatures from 50 to 120 °C on betalain retention and found that, at lower temperatures, there was lower degradation of these constituents, corroborating the results of the present study.…”
Section: Resultssupporting
confidence: 78%
“…Except for these few reports, there is no report on safety, biological activity, and bioavailability of the betalains processed through novel methods. However, some of these processing technologies have been proven to be beneficial in enhancing antioxidant activity or biological activity of extracted betalains (Krifa and others ;Kim and others ; Kannan ; Lee and others ; Gokhale and Lele ; Ravichandran and others ; Cruz‐Cansino and others ; Nunes and others 2015; Sravan Kumar and others ) due to enhanced co‐extraction of antioxidants such as flavonoids, and phenols. In addition, beetroot juice concentrates with high contents of neobetanin, a degradation product of betanin formed during processing, have been observed to lower postprandial insulin and glucose response (Wootton‐Beard and others ).…”
Section: Dietary Safetymentioning
confidence: 99%
“…It has been widely applied in order to optimize a product or process in many cases (Chang et al . ; Gokhale and Lele ; Hashemi Shahraki et al . ).…”
Section: Introductionmentioning
confidence: 99%